Study of viral load reduction in disposable face masks upon UV-C exposure using RT-qPCR - Sharfuddin, A.A.M (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.